Well-being at work and Finnish dairy farmers─from job demands and loneliness towards burnout - Kallioniemi, Marja K.; Kaseva, Janne; Kymäläinen, Hanna-Riitta; Hakanen, Jari J. (Frontiers in Psychology, 2022)
Novel information about the relationships between farmers’ job demands, burnout, and ill health is reported based on testing the so-called “health impairment process” of the Job Demands ─ Resources Model (JD-R) on a representative sample of Finnish dairy farmers. The aim was to find out whether three different job demand factors; workload, loneliness and societal demands were related to the indicators of ill health via burnout. The data is based on a postal survey of 400 Finnish dairy farms. Altogether 265 questionnaires were received from 188 farms and included in the analysis. The response rate was 47 per cent among sample farms. Structural equation modelling (SEM) was used to analyze the relationships between the variables. Explanatory factor analysis was used to group the job demand variables. We identified three job demand factors, which we labelled workload, loneliness, and societal demands. Our theoretical model was supported in that two of the factors, namely workload and loneliness, were related to ill health indirectly via burnout. In addition, workload was directly connected with ill health. Societal job demands were not significantly related to burnout, or to ill health. Our results suggest that farmers could benefit from means to reduce workload, especially the physical load. This topic needs further research as the restructuring process has increased farm enterprise sizes. There is a need to develop tools and projects to alleviate loneliness among farmers. Lack of social support, high workload, ill health, and burnout among farmers may have serious direct and indirect negative consequences for the sustainability of farming.